Importance of phosphorylation in PCSK9 processing, stability and function - Dewpura, Thilina (University of Ottawa (Canada), 2010)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a secreted glycoprotein regulating the degradation of low density lipoprotein receptor. Single nucleotide polymorphisms in PCSK9 associate with both hyper- and hypo-cholesterolemia; studies show significant reduction in risk of coronary heart disease for 'loss of function' PCSK9 carriers. We used a combination of mass spectrometry and radiolabeling to report that PCSK9 is phosphorylated at two sites, Ser47 in its propeptide, and Ser688 in its C-terminus. Site directed mutagenesis (SDM) demonstrated that a Golgi casein kinase-like kinase was responsible for PCSK9 phosphorylation based on the consensus site, SXE/S(p). PCSK9 phosphorylation is cell-type specific; phosphorylation status did not affect PCSK9 processing or secretion. Phosphorylated PCSK9 propeptide is protected against proteolysis. Immunoblotting demonstrated that PCSK9 mutants engineered by SDM to prevent phosphorylation at either site (substitution to Ala) or in combination resulted in significantly increased LDLR levels in HuH7 cells by up to -25%. PCSK9 mutants engineered by SDM to mimick phosphorylation (substitution to Asp/Glu) at the N-terminus, but not at the C-terminus or in combination, promoted LDLR degradation significantly more than wild-type. Far western analysis demonstrated that preventing PCSK9 phosphorylation promoted its interaction with the endogenous inhibitor Annexin A2.
Keywords: Chemistry, Biochemistry.